Short-Term and Long-Term Effects of COVID-19 and Remote Learning: Experiences of Parents Supporting Children with Mathematical Learning Disabilities in Israel - Sarit Ashkenazi; Sonia Hassoun (MDPI AG, 2024)
Background: Over the last three years, many studies have explored the effect of pandemic closures on learning. However, in Israel, the perspectives of parents on the short- and long-term effects of the lockdowns on students with mathematical learning disabilities (MD), have rarely been examined. Method: To fill this gap, MD (n = 33) or typically developing (n = 50) children were selected. They were in the 1st and 2nd grades during the closures, and we tested them and their surroundings, two years later. Results and Conclusions: First, according to the parent's survey, children with MD had physical conditions similar to the TD group, the two groups had similar stable connections to the internet, computer, and a quiet environment. However, MD children (1) needed more help and (2) had a harder time concentrating during virtual math classes compared to TD children. Moreover, the coronavirus closures resulted in a greater learning gap in the MD children compared to the TD children. We found positive associations between difficulties reported by the parents and actual weakness in performances in complex multiplication and division and verbal working memory.